Aplicativos de celular para o automanejo da dor musculoesquelética: uma revisão sistemática de lojas online do Brasil - Ribeiro, Luiz Filipe Máximo (Universidade Federal de São Carlos, 2025)
Musculoskeletal pain, a common and disabling condition. In Brazil, the prevalence of chronic pain ranging from 45% to 97% having a significant social and economic impacts. Mobile health (mHealth) applications are showing potential for musculoskeletal pain treatment. Assessing their quality is crucial to guarantee safety and efficacy. This dissertation is composed of one study, presented as follows: Objectives: Systematically assess the availability of mobile health applications for patients with musculoskeletal pain in Brazilian online stores and evaluate them with Mobile Health App Rating Scale (MARS) scale. Methods: Searches at App Store and Google Play and were performed in December 2024. Only smartphones applications in Portuguese, with no restrictions of price, name or version, involving the self-management of musculoskeletal pain (including education, exercises, counseling or monitoring of patient health) were included. The quality of applications was assessed using MARS. Two reviews did the identification, screening and mHealth assessment, and a third review decided in cases that disagreements occurred. This systematic review was previously registered at PROSPERO (CRD42024626484). Results: Out of the 12,639 applications identified, 36 met the inclusion criteria (App Store = 5 and Google Play = 31). Out of a total, (41.5%) applications approach exercises, (26.4%) education and counseling, (15.1%) symptom tracking, (15.1%) notes/diary, and (1.9%) self-massage. The overall MARS score ranged from 2.75 to 4.39, and the overall mean score and standard deviation was 3.87 ± 0.28. Conclusion: The mHealth applications for self-management available in Brazilian stores are of acceptable quality and functionality. However, other studies are necessary to evaluate the efficacy and effectiveness of these mobile health applications to the self-management of pain.
Mobile health applications for the self-management of musculoskeletal pain: a systematic review of online stores in Brazil
Keywords: Dispositivos celulares; Doenças musculoesqueléticas; Dor crônica; Manejo da dor; Tecnologias móveis de saúde; Chronic pain; MHealth technologies; Pain management; Musculoskeletal disorder; Smartphones; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL